The Relationship between Pharmaceutical Services and Satisfaction of Customers Accessing Pharmacy Services in Denpasar - Eka Arimbawa; Ketut Suarjana; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: Pharmaceutical care has been shifted from product or drug oriented paradigm into patient oriented to ensure that every customer will be able get the most effective medication. This research aims to explore the relationship between pharmaceutical services and satisfaction of customers accessing the pharmacy services in Denpasar. Methods: This research was analytic study using cross sectional design. The samples consisted of 116 customers taken from 20 pharmacies at Denpasar. Data was collected using self-administered questionnaires. Data was analyzed using logistic regression. Results: The analysis indicated that the level of customer satisfaction was 46.55%. There was a significant relationship between aspects of pharmaceutical services like pharmacy appearance (OR=12.819, 95%CI: 2.791-58.870), drug information services (OR=16.157, 95%CI: 3.279-79.620), the availability of drugs (OR=6.811, 95%CI: 1.571-29.460), and speed of service (OR=43.432, 95%CI: 7.197-262.095) with satisfaction levels of customers accessing the pharmacyservices. Conclusion: It is recommended that there is an upgrade of facilities in order to enhance customer satisfaction including an increase in staff numbers attending to customers that are able to provide adequate information so as to optimize service provision.